A 4-year prospective investigation of predictive effects of prepandemic sexual stigma, affective symptoms, and family support on fear of COVID-19 among lesbian, gay, and bisexual individuals - Huang, Mei-Feng; Chang, Yu-Ping; Chou, Wen-Jiun; Yen, Cheng-Fang (Frontiers in Public Health, 2024)
Aim This prospective study examined whether prepandemic sexual stigma, affective symptoms, and family support can predict fear of coronavirus disease 2019 (COVID-19) among lesbian, gay, and bisexual (LGB) individuals. Methods Data of 1,000 LGB individual on prepandemic sociodemographic characteristics, sexual stigma (familial sexual stigma [FSS] measured by the Homosexuality-Related Stigma Scale, internalized sexual stigma [ISS] measured by the Measure of Internalized Sexual Stigma for Lesbians and Gay Men, and sexual orientation microaggression [SOM] measured by the Sexual Orientation Microaggression Inventory), affective symptoms (i.e., depression measured by the Center for Epidemiologic Studies–Depression Scale and anxiety measured by the State–Trait Anxiety Inventory–State version), and family support measured by the Adaptability, Partnership, Growth, Affection, and Resolve Index were collected. Four years later, the fear of COVID-19 was assessed using the Fear of COVID-19 Scale and the associations of prepandemic sexual stigma, affective symptoms, and perceived family support on fear of COVID-19 4 years later were analyzed using multiple linear regression analysis. Results In total, 670 (67.3%) participants agreed and completed the follow-up assessment. Greater prepandemic FSS, ISS, SOM, affective symptoms, and perceived family support were significantly associated with a greater fear of COVID-19 at follow-up. Conclusion The identified predictors should be considered when designing interventions aimed at preventing and reducing the fear of COVID-19 in LGB individuals.